INDONESIAN SCIENTIFIC JOURNAL DATABASE: PENGENALAN - Tambunan, Kamariah (BACA: Jurnal Dokumentasi dan Informasi, 2012)
In line with the government's efforts to improve people's knowledge, Center of Scientific Documentation and Information - Indonesian Institute of Sciences (CSDI-IIS) has been developing database of information scientific works. One of the works is scientific journals. The development of digital technology increases the production of scientific information. In order to the information meets up the user quickly and accurately, it requires a database. Indonesian Scientific Journal Database (ISJD) as a database of scientific journals is the system for users to obtain the information. Users can easily obtain the information through ISJD.